2013
DOI: 10.1136/bmjopen-2013-003052
|View full text |Cite
|
Sign up to set email alerts
|

Does smoking cessation with varenicline worsen vascular endothelial function?

Abstract: ObjectivesA meta-analysis suggested that the use of varenicline, which is a partial agonist of nicotinic acetylcholine receptors and is effective in smoking cessation, increases the risk of cardiovascular events within 52 weeks of starting treatment. Defining these events as occurring during drug treatment (usually for 12 weeks) or within 30 days of discontinuation, another meta-analysis showed that the risk was statistically insignificant. In the present study, we aimed to clarify the effect of varenicline-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…As we previously reported, 11 each subject was treated with varenicline titrated up to 1.0 mg twice daily (0.5 mg once a day for the first 3 days, 0.5 mg twice a day for next 4 days and 1.0 mg twice a day for 11 weeks). The target smoking cessation date was planned to be within 7 days after the initiation of varenicline.…”
Section: Treatment With Varenicline and Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…As we previously reported, 11 each subject was treated with varenicline titrated up to 1.0 mg twice daily (0.5 mg once a day for the first 3 days, 0.5 mg twice a day for next 4 days and 1.0 mg twice a day for 11 weeks). The target smoking cessation date was planned to be within 7 days after the initiation of varenicline.…”
Section: Treatment With Varenicline and Study Proceduresmentioning
confidence: 99%
“…10 Recently, we reported that varenicline-assisted smoking cessation improved vascular endothelial function in patients with hypertension, diabetes and/or dyslipidemia who were eager to quit smoking. 11 However, we did not focus on the association between endothelial function and oxidative stress in that study. In the present study, we aimed to clarify whether varenicline-assisted smoking cessation worsens or improves oxidative stress as well as vascular endothelial function.…”
Section: Introductionmentioning
confidence: 98%
“…The observations suggest that in ceasing smokers, varenicline and smoking cessation do not lead to worsening of the vascular endothelial function. 46 Within the Asian population, there have been no reports of varenicline being associated with increasing serious cardiovascular AEs, 22 29 though further trials are needed to confirm this.…”
Section: Resultsmentioning
confidence: 99%
“…We collected the following clinicopathological factors for all the patients enrolled in this study: age, gender, tumor site, HPV‐L1 status, clinical stage (T, N, stage based on UICC 8th edition), Brinkman index of 200 as smoking behavior, irradiation dose and combination chemotherapy (Table ). The 40 specimens of the training set were collected during biopsies performed before treatment, immediately frozen in liquid nitrogen and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%